Population biology and reproductive characteristics of the hermit crab Pagurus minutus Hess, 1865 (Decapoda: Anomura: Paguridae) in the northern part of the species range (Peter the Great Bay, the Sea of Japan). Issue 8 (14th September 2018) - Korn, Olga M.; Kornienko, Elena S.; Selin, Nikolai I.
ABSTRACT: Population and reproductive characteristics of the hermit crab Pagurus minutus Hess, 1865 were examined in the northern part of the species range (Vostok Bay, Peter the Great Bay, the Sea of Japan). The average population density was 13 ± 4 SE ind/m 2 and did not change during the year; the average biomass was 12.56 ± 3.43 SE g/m 2 . Hermit crabs were found at a depth of 0–6 m, but were most numerous at 0–1 m in summer and at 2–3 m in winter, hence this species showed distinct seasonal migrations. The shield length of males varied from 1.0 to 7.0 mm and females from 1.1 to 4.7 mm. The population of P. minutus was signiﬁcantly female-biased. Females attained sexual maturity at a shield length of more than 1.1 mm. Ovigerous females were found from early May to early September. Pagurus minutus has no embryonic diapause, with the incubation period lasting about a month. The increase in the number of females with eggs at early developmental stages in July–August suggested that repeated ovipositions took place in summer. The prevalence of females in the population and their early maturation, multiple spawning, the release of larvae during the most favourable time for their development, and distinct vertical migrations allowing avoidance of the negative effect of the ice-cover, ensure high abundance of P. minutus in the northern part of the species range.